Changes in Hepatic Phospholipid Metabolism in Rats under UV Irradiation and Topically Treated with Cannabidiol - Michał Biernacki; Anna Jastrząb; Elżbieta Skrzydlewska (MDPI AG, 2021)
The liver is a key metabolic organ that is particularly sensitive to environmental factors, including UV radiation. As UV radiation induces oxidative stress and inflammation, natural compounds are under investigation as one method to counteract these consequences. The aim of this study was to assess the effect of topical application of phytocannabinoid-cannabidiol (CBD) on the skin of nude rats chronically irradiated with UVA/UVB, paying particular attention to its impact on the liver antioxidants and phospholipid metabolism. The results of this study indicate that CBD reaches the rat liver where it is then metabolized into decarbonylated cannabidiol, 7-hydroxy-cannabidiol and cannabidiol-glucuronide. CBD increased the levels of GSH and vitamin A after UVB radiation. Moreover, CBD prevents the increase of 4-hydroxynonenal and 8-iso-prostaglandin-F2α levels in UVA-irradiated rats. As a consequence of reductions in phospholipase A2 and cyclooxygenases activity following UV irradiation, CBD upregulates the level of 2-arachidonoylglycerol and downregulates prostaglandin E2 and leukotriene B4. Finally, CBD enhances decreased level of 15-deoxy-Δ-12,14-prostaglandin J2 after UVB radiation and 15-hydroxyeicosatetraenoic acid after UVA radiation. These data show that CBD applied to the skin prevents ROS- and enzyme-dependent phospholipid metabolism in the liver of UV-irradiated rats, suggesting that it may be used as an internal organ protector.